Electronic security systems : a manager's guide to evaluating and selecting system solutions - Pearson, Robert L. (Butterworth-Heinemann, 2007)
Electronic Security Systems is a book written to help the security professional understand the various electronic security functional components and the ways these components interconnect. Providing a holistic approach to solving security issues, this book discusses such topics as integrating electronic functions, developing a system, component philosophy, possible long-term issues, and the culture within a corporation. The book uses a corporate environment as its example; however, the basic issues can be applied to virtually any environment. For a security professional to be effective, he or she needs to understand the electronics as they are integrated into a total security system. Electronic Security Systems allows the professional to do just that, and is an invaluable addition to any security library. * Provides a well-written and concise overview of electronic security systems and their functions * Takes a holistic approach by focusing on the integration of different aspects of electronic security systems * Includes a collection of practical experiences, solutions, and an approach to solving technical problems.